Major Agronomical Research Works at the Institute of Agriculture and Animal Sciences, Rampur, Chitwan, Nepal: A Review - Amgain, LP; Timsina, J (Journal of the Institute of Agriculture and Animal Science, 2005)
The Institute of Agriculture and Animal Sciences (IAAS) under Tribhuvan University (TU) has been conducting various disciplinary and system research works, and publishing the findings through the IAAS Journal, IAAS Research Reports, and Nepalese Journal of Agriculture for over 25 years. A literature review was done to appraise the agronomical research works on major field crops and cropping systems at IAAS, Rampur, Chitwan, Nepal. The objectives were to summarize the results of various agronomic research works at the institute to determine the extent and causes of yield gaps of major crops, and to identify the future research priorities. The review revealed that the on-station research at IAAS in the past were conducted on 14 crops, on maize-and wheat-based systems and on 5 major themes. The main themes of research in most crops were varietal evaluation and breeding, crop management, soil management, weed management and pest management though in some crops research was conducted on other themes too. A total of 81 studies were conducted on various crops, of which 48 were on cereals, 14 on legumes, 10 on oilseed crops, and 6 on potato. There were 2 studies on wheat-based and a single study on maize-based systems. Average potential yields of rice, maize and wheat were 5.5, 4.4 and 5.0 t/ha, while research station yields and farmers' field yields of these crops were 3.4, 3.3 and 3.5 t/ha and 2.7, 1.8 and 1.9 t/ha, respectively, in Chitwan. The yield gaps between the potential and farmers' field for those crops were 2.76, 2.58 and 3.15 t/ha, while those between potential and research station yields were 2.1, 1.1 and 1.53 t/ha, respectively. The gaps between research station and farmers' field yields were much smaller in rice (0.66 t/ha) than in maize (1.48 t/ha) and wheat (1.62 t/ha). The results suggest that there is a great scope to raise yields of all cereals in farmers’ fields, more so for wheat and maize than for rice. Improved agronomical research on rice varieties and crop and soil management required to reduce the yield gap for rice, while adoption of recommended technologies by farmers would help reduce yield gap in wheat. For soybean, lentil, and potato, the gap between potential and farmers’ yields is much larger than the other yield gaps suggesting large scope for increase in yields in farmers’ fields through both improved management and improved varieties. Innovative and new researches on eco-region suited variety identification, improved crop and soil management, improved water and N management and on agro-meteorology and crop modeling are suggested as priorities for future research to uplift the productivity and reduce yield gaps of major crops in Chitwan district of Nepal. Key words: Field crops, on-station research, on-farm research, crop productivity, yield gap analysis J. Inst. Agric. Anim. Sci. 26:1-20 (2005)